Assessing the response and fragility of concrete bridges under multi-hazard effect of vessel impact and corrosion. (15th December 2020) - Fan, Wei; Sun, Yang; Yang, Cancan; Sun, Wenbiao; He, Yang
Highlights: A vulnerability analysis framework is developed to for RC bridge structures under multi-hazard effect of vessel collisions and corrosions. The modeling method considering bond-slip behavior is developed and validated to predict the impact and post-impact behavior of RC columns. Corrosion deterioration has a significant influence on the vessel-impact performance of bridge structures. Significant differences are identified for the damage evolution of the deteriorated bridge under barge impacts and ship impacts. Abstract: Bridges crossing navigable waterways have a high risk for vessel collision hazard, and are meanwhile experiencing significant 'aging' hazard due to the surrounding aggressive environments. These bridges must be designed to be resilient to both episodic (vessel collision) and chronic (structural deterioration) hazards. To achieve this goal, this paper will develop a novel fragility assessment framework for reinforced concrete (RC) bridges under vessel collision with the corrosion-induced structural deterioration being considered. The cornerstone of this fragility assessment framework is the computational model with the capability of accurately predicting vessel impact response and corrosion-induced deterioration measures. In doing so, detailed finite element (FE) modeling approaches, including reinforcement bond-slip effects, are firstly developed and validated by the experimental results. The effects of corrosion are characterized by a series of deterioration measures that can be implemented into FE models. These FE modeling approaches were utilized to model the baseline bridge. Three different exposure periods (i.e., 0, 50, and 100 years) and two types of vessel (barge and ship) are considered. Driven by the response data generated by the FE model, a surrogate model is developed to feature both accurate vessel-impact response estimates and negligible computation cost. This surrogate model is then employed to create fragility curves using Monte Carlo methods. Fragility analysis results have indicated the significant role played by corrosion in increasing the vulnerability of RC bridges under vessel collision throughout the lifetime of the baseline bridge. The probability of bridge collapse rises by almost 100% near the end of the bridge's life. Significant differences were found for the damage evolution of the deteriorated bridge under barge impacts and ship impacts. Particular critical impact speeds were observed in the barge-impact response, but not during ship collisions.